2021
DOI: 10.1016/j.sleep.2021.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea (OSA) and outcomes from coronavirus disease 2019 (COVID-19) pneumonia: a systematic review and meta-analysis

Abstract: Background Obstructive sleep apnea (OSA) is the most prevalent sleep-related breathing disorder which could impair someone's quality of life and is also associated with poor outcomes from many diseases. Currently, the evidence regarding the link between OSA and coronavirus disease 2019 (COVID-19) is still conflicting. This study aims to analyze the relationship between OSA and poor outcomes of COVID-19. Materials and Methods We systematically searched the PubMed and Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 45 publications
3
58
0
Order By: Relevance
“…Finally, obesity results in physiological lung alterations, such as decreased functional residual capacity and hypoxemia [ 67 ]. In addition, obstructive sleep apnoea hypopnea syndrome (OSAHS) increases adverse outcomes of COVID-19 [ 68 ]. The etiology of OSAHS is complex, and obesity is one of the main causes of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, obesity results in physiological lung alterations, such as decreased functional residual capacity and hypoxemia [ 67 ]. In addition, obstructive sleep apnoea hypopnea syndrome (OSAHS) increases adverse outcomes of COVID-19 [ 68 ]. The etiology of OSAHS is complex, and obesity is one of the main causes of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…contribute to the development of severe form of Covid-19, causing further inflammation and immune dysfunction that leads to the formation of cytokines storm which is life threatening. [2][3][4][5][6][7] Several therapies had been proposed to control and manage these conditions. [8][9][10][11][12][13][14] Recently the use of GLP1-RA, as one alternative to treat DM patients, had shown promising effect to reduce excessive inflammation-induced acute lung injury and improving Covid-19 outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with comorbidities such as obesity, diabetes, chronic respiratory disease, cardiovascular disease and other immunocompromising conditions are facing higher risks in developing the severe form of SARS‐CoV‐2 infections. 4 , 5 , 6 , 7 , 8 , 9 For the past months, medical therapies to treat Covid‐19 have been growing and evolving rapidly, ranging from supportive care, antivirals, anti‐inflammatory agents and possible supplementations such as vitamin D. 10 , 11 , 12 , 13 Several studies have shown that vitamin D has antiviral properties and potential roles against acute lung injury or ARDS, making large interest on vitamin D has rapidly emanated even in the early beginning of pandemic. 14 , 15 Low vitamin D serum levels is associated with an increase in inflammatory cytokine levels and significant increase of risk to develop pneumonia and viral respiratory tract infections, which both contribute to the development of ARDS.…”
Section: Introductionmentioning
confidence: 99%